Rantai Pasokan Produk Tumbuhan Gaharu (Aquilaria spp.) asal Merauke, Papua - Gono Semiadi; Harry Wiriadinata; Eko B. Waluyo; Dedy Darnaedi (Buletin Plasma Nutfah, 2010)
Papua is Claimed to Have High Production of Gaharu (Aquilaria spp.) that is Mainly Extracted from Swamp Areas. However, it is still a polemic whether this claim is true and what is the real production level. Therefore, a field survey was conducted in Jayapura and Merauke (Papua) and Probolinggo (East Java) to unveil the actual condition of the gaharu production and its condition. Interviews were made with local forestry officers (BBKSDA) and local traders in Jayapura and Merauke, shipping companies, warehouse administrators and port administrators in Probolinggo, East Java as the final destination sea port. The results showed that the gaharu taken from swamp areas in the region of Merauke was proven by BBKSDA officials. In one year, the legal production of gaharu in the form of kamedangan reached 100 tons, while similar amount was thought to be slipped away in the illegal trades. Field survey in 2007 conducted by local BBKSDA officers in Asmat and Mappi districts showed a high production of gaharu in the form of wet kamedangan. Gaharu sea freighters at least carried 175 sacks/trip, with special freighters could carry up to 2.100 sacks/trip. The mean weight of each sack was between 58-90 kg with the mean water content ranged from 54-87.39%. Special quota criteria is required to be established on the basis of its quality for Merauke region to avoid problems on undervalue or misconception of the products and production level. Verification on the gaharu tree species originated from Papua region is also still needed. AbstrakPapua merupakan salah satu wilayah yang memiliki area produksi gaharu (Aquilaria spp.) yang sangat luas. Disinyalir produksi utama panenan gaharu dalam bentuk kamedangan di Merauke berasal dari daerah rawa. Namun informasi tersebut masih diragukan. Untuk itu dilakukan survei lapang ke Jayapura dan Merauke (Papua) dan Probolinggo (Jawa Timur) guna memahami kondisi sebenarnya tentang potensi gaharu. Responden yang diwawancari mencakup petugas BBKSDA dan pengumpul besar di Jayapura dan Merauke, perusahaan ekspedisi, petugas gudang pengumpulan dan administrator pelabuhan di Probolinggo. Hasil survei menunjukkan bahwa produksi utama panenan gaharu di Merauke yang berasal dari dalam rawa merupakan sisa produk tebangan masa lampau. Dalam satu tahun pengeluaran resmi gaharu dari wilayah BBKSDA Papua mencapai 100 ton. Sedangkan jumlah pengeluaran secara ilegal diperkirakan mencapai angka yang hampir sama. Hasil survei lapang ke Kabupaten Asmat dan Mappi yang dilakukan BKSDA seksi wilayah I Merauke pada tahun 2007 menunjukkan produksi kamedangan di kedua wilayah tersebut cukup tinggi. Satu kapal barang sedikitnya membawa 175 karung gaharu, sedangkan pada kapal khusus pengangkut gaharu dapat mencapai 2.100 karung. Produksi gaharu dari dua kabupaten tersebut seluruhnya diangkut lewat laut ke Probolinggo. Bobot per karung kamedangan maupun abuk gaharu mencapai 58-90 kg, dengan kandungan air 54-87,4%. Kriteria penetapan kuota asal Merauke perlu diperhatikan agar terhindar dari masalah terlalu rendahnya perkiraan produksi atau salah pengertian mengenai produk dan potensi produksi yang ada. Selain itu verifikasi jenis tanaman gaharu asal Papua masih diperlukan.